TRANSFORMATION OF ARTS EDUCATION CURRICULUM THROUGH POSTMODERN THINKING - Abdul Halim Bin Husain (Fakultas Bahasa dan Seni Universitas Negeri Padang, 2014)
The modern age, which sounds as if it would last forever, is fast becoming a thing of the past. Industrialization is quickly giving way to post-industrial, factory labour to home and office work and, in the arts, the Tradition of the New is leading to the combination of many traditions. Even those who still call themselves Modern artists and architects are looking backwards and sideways to decide which styles and values they will continue (Jenecks, 1986). Keywords: arts education, curriculum, postmodern thinking.